Legal Politics in the Formation of a New Civil Procedure Law - Setyowati, Retno Kus (UNISSULA, 2025)
The purpose of this study is to analyze the politics of law in the formation of a new civil procedural law. The current civil procedural law was formed by the Dutch East Indies government which is still valid based on Article II of the Transitional Rules of the 1945 Indonesian Constitution, and is complemented by other laws and regulations scattered in various laws and regulations. This legal research is Normative legal research. The approach method used is the statutory approach. The results of this study found that the regulations governing civil procedural law are the Herziene Indonesich Reglement, Rechtreglement voor de Buitengewesten, Reglement op de Burgerlijk Rechtsvordering, as well as various other laws and regulations and also the Supreme Court Circular Letter, Supreme Court Regulation. With the spread of various laws and regulations, it results in overlapping. For this reason, it is necessary to immediately organize it into one complete and systematic regulation, so that it can create the principle of fast, simple and low-cost justice.